Penerapan Naqli Dan Aqli : Kajian Terhadap Kurikulum Program Tamhidi Syariah Dan Undang-undang - Rasmina Hasbullah; Azniwati Abdul Aziz; Wan Amir Nudin Wan Ishak; Sanusi Shariff; Mohammed Akhiruddin Ibrahim; Irwan Mohd Subri (GAE-Global Academic Excellent, 2024)
Non-Indexed Publication